2018
DOI: 10.1007/s00414-018-1912-7
|View full text |Cite
|
Sign up to set email alerts
|

Whose blood is it? Application of DEPArray™ technology for the identification of individual/s who contributed blood to a mixed stain

Abstract: The interpretation and statistical evaluation of mixed DNA profiles often presents a particular challenge in forensic DNA investigations. Only in specific combinations can single cellular components of a mixture be assigned to one contributor. In this study, the DEPArray™ technology, which enables image-assisted immunofluorescent-sorting of rare single cells using dielectrophoretic (DEP) forces, was applied together with different preliminary tests to identify the individual/s who contributed blood to a given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…In particular, whole genome amplification of single CTCs and WBCs was carried out to confirm the absence of WBC contamination by DNA finger printing . Besides, similar results have been published in other application domains, where direct DNA fingerprinting of individual and pools of cells collected by DEPArray™ from forensic evidence has shown achievement of 100% purity .…”
Section: Accuracy Of Deparray™supporting
confidence: 54%
“…In particular, whole genome amplification of single CTCs and WBCs was carried out to confirm the absence of WBC contamination by DNA finger printing . Besides, similar results have been published in other application domains, where direct DNA fingerprinting of individual and pools of cells collected by DEPArray™ from forensic evidence has shown achievement of 100% purity .…”
Section: Accuracy Of Deparray™supporting
confidence: 54%
“…10. and highly probative log (LR)s were recovered by DSCS from every donor (range [13][14][15][16][17][18][19][20][21][22][23][24]. No standard bulk mixture analysis results were available for comparison with this mixture due to computational limitations.…”
Section: Dscs Applied To Complex Mixturesmentioning
confidence: 99%
“…A potential solution to overcoming the issue of genotype information loss is to separate individual cells or a small subset of cells from the original 'bulk' mixture prior to analysis [10,[14][15][16][17][18][19][20][21]. Doing so may result in single source DNA profiles for all contributors as well as new 'mini mixtures' with less complexity compared to the original bulk mixture due to a decrease in the NOC [10].…”
Section: Introductionmentioning
confidence: 99%
“…A previous report has shown that isolation of multiple groups of cells from mixtures results in sub-populations with differing constituent weight ratios [ 6 ] that, in combination, can recover more DNA profile information, while others have demonstrated the potential to obtain highly probative single source samples from mixtures following analysis of recovered single or multiple cell subsets [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. One of these latter physical cell recovery methods (direct single cell subsampling, DSCS) allows for multiple physical subsamplings of individual cells (or cell subsets) from complex cellular DNA mixtures using a stereomicroscope and tungsten needle.…”
Section: Introductionmentioning
confidence: 99%